Integrated language and computer laboratory model in efficiency of arabic language practicum and digital hadith studies: A systematic literature review - Muhammad Irfan Faturrahman; Muh. Alif Kurniawan; Yunahar Octa Syaftian; Arrafi Jihad Al Kahfi (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2026)
Purpose - This study aims to formulate an integrated laboratory model that combines the capabilities of language laboratories and computer laboratories to optimize practicum efficiency in the fields of Arabic Language Learning and Digital Hadith Studies. Design/methods/approach - This study adopted a qualitative Systematic Literature Review (SLR) following the PRISMA framework. Literature was collected from Crossref and Google Scholar through the Publish or Perish application. Of the 1,200 records identified, 15 relevant journal articles published between 2015 and 2025 met the selection criteria and were analyzed using content analysis and thematic synthesis. Findings - Based on the thematic synthesis, this study formulated three adaptive laboratory integration models: (1) the Hybrid Model, which integrates Hadith text corpus computing with oral communication competencies; (2) the Research Incubator Model, which positions the laboratory as a collaborative interdisciplinary research environment based on digital datasets; and (3) the Multilingual Accessibility Model, which focuses on the development of digital religious products, such as Hadith software applications. Research implication/limitation - Conceptually, the implementation of these three integration models has the potential to minimize operational redundancy and enhance instructional support capacity. However, this study is limited by its reliance on metadata obtained exclusively from Crossref and Google Scholar, without incorporating other globally indexed high-impact databases such as Scopus or Web of Science. Consequently, further empirical validation is required before large-scale implementation can be recommended. Originality/value - This study contributes a novel conceptual framework for integrating laboratory facilities that bridges applied linguistics and digital religious text studies. This aspect of academic governance remains relatively underexplored within conventional laboratory models that operate as separate and independent units.